235k views
1 vote
PLEASE HELP ASAP I REALLY NEED IT !!!!!!

PLEASE HELP ASAP I REALLY NEED IT !!!!!!-example-1
User Anstrong
by
5.6k points

1 Answer

0 votes

Answer:

-2 × (7x + 1) -5 × (3x² + 3x + 2) is equivalent to -15x² - 29x - 12 .

(-7x² -21x + 13) - (8x² + 8x + 25) is equivalent to -15x² - 29x - 12 .

Explanation:

As given the expression in the question be as follow .

= -15x² - 29x - 12

First part

= (-19x² -4x -7) + (4x² + 25x - 5)

First open the bracket

= -19x² -4x -7+ 4x² + 25x - 5

= -19x² + 4x² -4x + 25x -7 - 5

= -15x² +21x - 12

Thus (-19x² -4x -7) + (4x² + 25x - 5) is not equivalent to -15x² - 29x - 12 .

Second part

= (-17x² + 2x -3) + (2x² - 31x - 9)

First open the bracket

= -17x² + 2x² + 2x -31x -3 -9

= -15x² - 29x - 12

Thus (-17x² + 2x -3) + (2x² - 3x - 9) is not equivalent to -15x² - 29x - 12 .

Third part

= -2 × (4x - 15) -3 × (5x² + 7x + 6)

First open the bracket and simplify the above terms

= -8x + 30 -15x² -21x -18

= -15x² -29x + 12

Thus -2 × (4x - 15) -3 × (5x² + 7x + 6) is not equivalent to -15x² - 29x - 12 .

Forth Part

= (5x² - 10x + 8) - (10x² + 19x + 20)

First open the bracket

= 5x² - 10x² - 10x - 19x + 8 - 20

= -5x² - 29x -12

Thus (5x² - 10x + 8) - (10x² + 19x + 20) is not equivalent to -15x² - 29x - 12 .

Fifth part

= -2 × (7x + 1) -5 × (3x² + 3x + 2)

First open the bracket

= -14x -2 -15x² -15x -10

= -15x² -29x -12

Thus -2 × (7x + 1) -5 × (3x² + 3x + 2) is equivalent to -15x² - 29x - 12 .

Sixth part

= (-7x² -21x + 13) - (8x² + 8x + 25)

Firsr open the bracket

= -7x² -21x + 13 - 8x² - 8x - 25

= -15x² -29x - 12

Thus (-7x² -21x + 13) - (8x² + 8x + 25) is equivalent to -15x² - 29x - 12 .

User Nebiyou Yismaw
by
5.0k points